1997
DOI: 10.1098/rstb.1997.0011
|View full text |Cite
|
Sign up to set email alerts
|

Marine sulphur emissions

Abstract: SUMMARYThe principal volatile sulphur species found in seawater are dimethyl sulphide (DMS), carbonyl sulphide (COS) and carbon disulphide (CS # ). Of these, DMS is the most abundant and widespread in its distribution. The predominant oceanic source of DMS is dimethylsulphoniopropionate (DMSP), a compatible solute synthesized by phytoplankton for osmoregulation and\or cryoprotection. Not all species have the same ability to form DMSP ; for example, diatoms generally produce little, whereas prymnesiophytes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
112
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(114 citation statements)
references
References 63 publications
0
112
0
2
Order By: Relevance
“…The main acids in the atmosphere, sulfuric and nitric acids, are generated by the oxidation of sulfur and N gases emitted by biogenic, volcanic, and anthropogenic sources (16)(17)(18), the latter of which is dominant at present. It has been noted that there is a higher fraction of LIP in polluted air masses (39,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main acids in the atmosphere, sulfuric and nitric acids, are generated by the oxidation of sulfur and N gases emitted by biogenic, volcanic, and anthropogenic sources (16)(17)(18), the latter of which is dominant at present. It has been noted that there is a higher fraction of LIP in polluted air masses (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…These precursor species can be the result of natural processes, such as the oxidation of dimethyl sulfide released by phytoplankton in oceanic surface waters (16), volcanic eruptions (17), or lightning. However, at present, the main source of such gases in the northern hemisphere is anthropogenic (18).…”
Section: Significancementioning
confidence: 99%
“…The main exception is dimethyl sulfide (DMS), which is known to be produced biogenically in the ocean [8,9] and yields the inorganic aerosol component sulfate upon complete oxidation in the atmosphere. [10,11] Isoprene, the strongest terrestrial biogenic emission, has also been observed as an oceanic emission [12] and in laboratory based studies of plankton.…”
Section: Introductionmentioning
confidence: 99%
“…As SO 2 is rapidly oxidised and either rained out or deposited to particles its impact on the sulphur budget is largely regional rather than global; therefore dimethyl sulphide (DMS), mainly dominated by the smaller biogenic inputs (Liss et al, 1997), is the major source of oxidised sulphur compounds at high southern latitudes away from direct continental source emissions of SO 2 (Gondwe et al, 2003). Once in the troposphere the nonsea salt sulphate particles (nss-SO 2− 4 ) and methane sulphonic acid (MSA), resulting from the oxidation of DMS, are the main sources of cloud condensation nuclei (CCN) which is believed to alter the radiation budget of the earth affecting the surface temperature and climate (Charlson et al, 1987).…”
Section: Introductionmentioning
confidence: 99%